Say everything that should be said! But how? Giving the body a voice. - Messeguem, Salah; Harig , Fatima Zohra; Ben Achour, Nadia (El Omda in Linguistics and Discourse Analysis, 2021)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-(--header-height)" dir="auto" data-turn-id="20fd17fa-6391-4954-ae77-cc16aecc1019" data-testid="conversation-turn-37" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:093330e1-5036-4b2c-bddb-c890e62da851-18" data-testid="conversation-turn-38" data-scroll-anchor="false" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="962d0806-9612-4d51-9064-fc79903cbd58" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> This article aims to reveal the suffering body and to explore its own voice in order to ensure communication when language fails to convey the essence of the message. Hence, there emerges a need to personify the body and grant it speech so that it becomes a witness to the human experience. This approach represents a necessity that has led many writers, inspired by this new representation of the soul, to give free rein to their pens in order to connect the body with artistic and literary expression.